32‐4: High transparent Active matrix Mini‐LED Full Color Display with IGZO TFT Backplane. Issue 1 (29th May 2019) - Fan, Jack; Lee, Chia-Yu.; Chen, Shu-jhih; Gang, Liu Ming; Jun, Zhang Li; Yang, Sun; Cai, Lu Ma; Fei, Xie Hua; Nian, Liu; Shi, Jianqing; Shen, Chongyu; Liu, Jay Guoxu
Abstract : In this paper, we presented a active matrix mini‐LEDs full color display with high transmittance over 60%. An 8‐inch display with RGB mini‐LEDs with top gate structure IGZO TFT backplane was demonstrated, which is 46 PPI and 256 grayscales and the pixel pitch is less than 0.55mm. It is the first time to realized the full color display based on RGB mini‐LEDs and chip on glass with top gate structure IGZO TFT backplane. We believe that it is a good breakthrough and demonstration for developing large‐size Micro LED backplane and displays.